Unraveling vertical inhomogeneity in vapour phase polymerized PEDOT:Tos films. Issue 36 (26th August 2020) - Chen, Shangzhi; Petsagkourakis, Ioannis; Spampinato, Nicoletta; Kuang, Chaoyang; Liu, Xianjie; Brooke, Robert; Kang, Evan S. H.; Fahlman, Mats; Crispin, Xavier; Pavlopoulou, Eleni; Jonsson, Magnus P.
Abstract : Vertical inhomogeneity found in vapour phase polymerized thin films of the conducting polymer PEDOT:Tos. Abstract : The conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT) forms a promising alternative to conventional inorganic conductors, where deposition of thin films via vapour phase polymerization (VPP) has gained particular interest owing to high electrical conductivity within the plane of the film. The conductivity perpendicular to the film is typically much lower, which may be related not only to preferential alignment of PEDOT crystallites but also to vertical stratification across the film. In this study, we reveal non-linear vertical microstructural variations across VPP PEDOT:Tos thin films, as well as significant differences in doping level between the top and bottom surfaces. The results are consistent with a VPP mechanism based on diffusion-limited transport of polymerization precursors. Conducting polymer films with vertical inhomogeneity may find applications in gradient-index optics, functionally graded thermoelectrics, and optoelectronic devices requiring gradient doping.